Kinetics and mechanistic insights into the hydrothermal synthesis of alumina microrods. (23rd November 2021) - Lin, Jianyang; Yang, Zhirong; Zhao, Xingqiang; Ji, Honghai; Peng, Chong; Sui, Baokuan; Chen, Wenyao; Zhang, Jing; Qian, Gang; Zhou, Xinggui; Duan, Xuezhi
Highlights: Influencing factors on the growth direction of alumina microrods were clarified. Kinetics equations of alumina microrods in each synthesis stages were established. The extended LaMer theory was improved to explain the gel nucleation process. Abstract: Understanding the growth kinetics and mechanism of alumina microrods is of great importance for controllable synthesis. In this work, alumina microrods with controllable morphology are hydrothermally synthesized to investigate the influence of reaction conditions on the growth mechanism which is supported by the reaction kinetics. The evolution kinetics of gel nucleation are established by tracing the change in the Al(OH)4 − ligand and AlOOH monomer concentrations. The driving force of the axial growth of alumina microrods is primarily affected by the reaction temperature and reaction time, and the aspect ratio is regulated by reactant concentration. The oriented growth from Al(OH)4 − ligands to alumina microrods and Ostwald ripening from small boehmite spherical particles on the microrod surface successively control the perfection of the crystal surface. It verifies that the nucleation kinetics of microrods are driven by the supersaturation of the gel ligands and improves the LaMer theory with specific kinetic equations.